Noncardiac anomalies in children with congenital heart disease - Xianghui Huang; Xianghui Huang; Yuan Gao; Yuan Gao; Weicheng Chen; Weicheng Chen; Wei Sheng; Wei Sheng; Wei Sheng; Guoying Huang; Guoying Huang; Guoying Huang (Frontiers in Cardiovascular Medicine, 2023)
IntroductionNoncardiac anomalies (NCAs) in patients with congenital heart defects (CHDs) are crucial for perioperative management and etiology studies. This study aimed to investigate NCAs in Chinese children with CHDs.MethodsMedical records for CHD-diagnosed children hospitalized from 1 January 2015 to 31 December 2019 were collected and subjected to retrospective analyses to excavate potential association rules between CHDs and noncardiac malformations.ResultsA total of 3,788 CHD patients were included in this study. The main phenotypes of CHD were Ventricular Septal Defect (VSD, 33.69%), Atrial Septal Defect (ASD, 12.72%), and Tetralogy of Fallot (TOF, 5.54%). A total of 887 (23.42%) cases showed noncardiac anomalies, which were mainly associated with the central nervous system (34.61%), nose/ear/mandibular/face (19.39%), genitourinary system (15.78%), and musculoskeletal system (15.56%). Compared to other CHD subtypes, septal defects had a lower percentage of associated NCAs (P = 3.7 × 10−9) while AVSD had a higher percentage (P = 0.0018).DisscussionNCAs are prevalent among CHD-diagnosed children in China, and the spectrums of NCAs in different CHD subcategories were different.